2016
DOI: 10.1038/cdd.2016.139
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of caspase-6 by HIP14 regulates its activation

Abstract: Caspase-6 (CASP6) has an important role in axonal degeneration during neuronal apoptosis and in the neurodegenerative diseases Alzheimer and Huntington disease. Decreasing CASP6 activity may help to restore neuronal function in these and other diseases such as stroke and ischemia, where increased CASP6 activity has been implicated. The key to finding approaches to decrease CASP6 activity is a deeper understanding of the mechanisms regulating CASP6 activation. We show that CASP6 is posttranslationally palmitoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…Caspase-6 (CASP6), another important player in apoptosis, has also been shown to be S-acylated, in this case by zDHHC17 (Skotte et al 2017). Reduced CASP6 S-acylation resulted in increased CASP6 activity, and vice versa (Skotte et al 2017).…”
Section: Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-6 (CASP6), another important player in apoptosis, has also been shown to be S-acylated, in this case by zDHHC17 (Skotte et al 2017). Reduced CASP6 S-acylation resulted in increased CASP6 activity, and vice versa (Skotte et al 2017).…”
Section: Cell Deathmentioning
confidence: 99%
“…Caspase-6 (CASP6), another important player in apoptosis, has also been shown to be S-acylated, in this case by zDHHC17 (Skotte et al 2017). Reduced CASP6 S-acylation resulted in increased CASP6 activity, and vice versa (Skotte et al 2017). Importantly, CASP6 was shown to play a critical role in neurodegenerative diseases such as Alzheimer disease (AD) and Huntington disease (HD) (Graham et al 2011) and zDHHC17 is known to also play a direct role in HD by mediating the S-acylation of huntingtin (Singaraja et al 2002;Huang et al 2004).…”
Section: Cell Deathmentioning
confidence: 99%
“…Hip14 was originally identified in the context of its interaction with the Huntington's disease-associated Huntingtin protein 42 . Since its discovery, hundreds of potential Hip14 palmitoylation substrates and interacting partners have been identified 34,35,[43][44][45][46][47][48][49][50] .…”
Section: Hip14 Acts Independently Of Previously Identified Regulatorsmentioning
confidence: 99%
“…HIP14 knockout leads to increased apoptosis, whereas HIP14 overexpression results in decreased apoptosis due to reduced NF-κB activation (12). Another study indicated that caspase 6, which plays an important role in apoptosis, can be inhibited by the palmitoyl transferase activity of HIP14 in the mouse brain (93). However, further investigation is needed to clarify whether this effect also occurs in pancreatic beta-cells.…”
Section: Hip14mentioning
confidence: 99%